The Representation of Religious Values as Character Education Messages in the Song “Senandung Ma’had Sunan Ampel al-‘Ali” - Rosyidah, Inayatur; Gufron, Gufron; Fitrotulloh, Mohamad Rofik (Universitas Muhammadiyah Mataram, 2026)
Character education in contemporary educational discourse extends beyond cognitive attainment to include value orientation, moral attitudes, and spiritual awareness. Within this context, symbolic media such as songs play an important role in engaging affective and cultural dimensions. This study examines the representation of religious values as character education messages in the song “Senandung Ma’had Sunan Ampel al-‘Ali,” a symbolic element of Ma’had al-Jāmi‘ah at UIN Maulana Malik Ibrahim Malang. This study employs a qualitative text-centered design using qualitative content analysis integrated with thematic analysis. The analysis is guided by character education theory and Islamic ethical perspectives. The data consist of the complete song lyrics, analyzed through coding, categorization, and interpretive meaning construction. Analytical rigor was ensured through theoretical triangulation, peer debriefing, and iterative coding verification. The findings identify five core values: devotion-oriented religiosity, appreciation of knowledge as a spiritual value, sincerity and dedication, moral struggle (jihad) as an ethical ethos, and social morality reflected in the concept of ulul albab. These values are constructed through symbolic and affective language, positioning the song as a medium for implicit value internalization. The study indicates that institutional song lyrics function as symbolic discourse through which religious values are organized and communicated, highlighting the role of affective-cultural media in character education.